Effects of Digital Teaching Materials on Physics Learning Outcomes for High School Students: A Systematic Literature Review - Salsabilla Mulya Putri; Muhammad Hasan Fadli; Festiyed; Asrizal (Jurnal Penelitian Pembelajaran Fisika, 2026)
The development of digital technology encourages the utilization of digital teaching materials in physics learning to enhance the effectiveness of the learning process. This research focuses on identifying the influence of digital teaching materials on physics learning in senior high schools. The research was conducted using a Systematic Literature Review (SLR) method. Six national articles published between 2021–2025 were analyzed based on theme suitability, quality, and empirical findings. The study results show that digital teaching materials such as e-modules, E-LKPD, interactive presentations, and application-based visual media have been proven to improve student learning outcomes, motivation, and critical thinking skills. The use of digital media also facilitates understanding of concepts and increases student activity through more engaging and interactive presentations. Thus, digital teaching materials have a positive influence and are worthy of integration into high school physics learning to support adaptive and technology-relevant education.